Exchange rate linkages between the ASEAN currencies, the US dollar and the Chinese RMB - Guglielmo Maria Caporale; Luis A. Gil-Alana; Kefei You (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper investigates whether the RMB is in the process of replacing the US dollar as the anchor currency in nine ASEAN countries, and also the linkages between the ASEAN currencies and a regional currency unit. A long-memory (fractional integration) model allowing for endogenously determined structural breaks is estimated for these purposes (Gil-Alana, 2008). The results suggest that the ASEAN currencies are much more interlinked than previously thought, whether or not breaks are taken into account, which provides support for a regional currency index as an anchor. Moreover, incorporating a break shows that the linkages between these currencies and the RMB and the US dollar respectively are equally important, and in fact in recent years the former have become stronger than the latter. Therefore including the RMB in the regional index should be considered.
Keywords: F31; C22; 330; ASEAN currencies; Chinese RMB; US dollar peg; fractional integration; breaks